Nonhemorrhagic Adrenal Infarction With Magnetic Resonance Imaging Features During Pregnancy. Issue 4 (October 2015) - Guenette, Jeffrey P.; Tatli, Servet
Abstract : BACKGROUND: Adrenal infarction is an infrequent cause of severe abdominal pain during pregnancy. The magnetic resonance imaging (MRI) features of adrenal infarction have not previously been thoroughly described. CASES: A 20-year-old woman, gravida 1 para 0, presented at 27 4/7 weeks of gestation with sudden-onset right upper quadrant and flank pain. A 29-year-old woman, gravida 2 para 1, presented at 17 5/7 weeks of gestation with sudden-onset right abdominal and flank pain and again at 35 5/7 weeks of gestation with sudden-onset severe left flank and upper quadrant pain. In both patients, unilateral adrenal infarction was diagnosed on contrast-enhanced computed tomography after initial nondiagnostic ultrasonography and MRI. Clinical presentation and MRI features of nonhemorrhagic adrenal infarction are described. CONCLUSION: Nonhemorrhagic adrenal infarction may be an underdiagnosed cause of acute abdominal pain during pregnancy and can be diagnosed with MRI. Abstract : Adrenal infarction may be an underdiagnosed cause of severe abdominal pain during pregnancy and can be diagnosed with magnetic resonance imaging.